(untitled) - Smith, D. Gordon (New York, 2008)
Reflecting changes in the structure of contemporary business enterprise, Business Organizations: Cases, Problems, and Case Studies, now in a Second Edition, uses case law, problems, and case studies to examine the role and purview of law in real-life business transactions.
Keywords: Business enterprises,Corporation law; Law and legislation; United States,United States